2017
DOI: 10.1200/jco.2016.70.1961
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Androgen Receptor Splice Variant-7 mRNA Detection in Circulating Tumor Cells of Men With Metastatic Castration-Resistant Prostate Cancer Treated With First- and Second-Line Abiraterone and Enzalutamide

Abstract: Purpose We reported previously that the detection of androgen receptor splice variant-7 (AR-V7) mRNA in circulating tumor cells (CTCs) correlated with poor outcomes from the use of abiraterone and enzalutamide in patients with castration-resistant prostate cancer (CRPC). Here, we expanded our cohort size to better characterize the prognostic significance of AR-V7 in this setting. Methods We prospectively enrolled 202 patients with CRPC starting abiraterone or enzalutamide and investigated the prognostic value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
356
8
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(396 citation statements)
references
References 12 publications
23
356
8
4
Order By: Relevance
“…In addition, heterogeneity among CTCs can be easily visualized. Although the AR-V7 mRNA expression is shown to correlate with worse clinical outcomes in recent literature, we cannot simply conclude that every mRNA transcript will be translated to protein (31 ). Indeed, Scher et al showed that resistance toward novel hormonal therapy (NHT) depends on the nuclear-specific location of AR-V7 protein rather than on cytoplasmic localization (32 ).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, heterogeneity among CTCs can be easily visualized. Although the AR-V7 mRNA expression is shown to correlate with worse clinical outcomes in recent literature, we cannot simply conclude that every mRNA transcript will be translated to protein (31 ). Indeed, Scher et al showed that resistance toward novel hormonal therapy (NHT) depends on the nuclear-specific location of AR-V7 protein rather than on cytoplasmic localization (32 ).…”
Section: Discussionmentioning
confidence: 87%
“…deny v tab. 4, všechny rozdíly byly statisticky signifikantní [11]. U pa cientů s CTC AR-V7+ bylo PFS zkráceno na dobu 4 vs. 10,1 měsíce ve skupine CTC AR-V7-.…”
Section: Historie Protokol Výhodyunclassified
“…Antonarakis et al [11] 202 149 (73,7 %) 36 (29,0 %) 113 (56 %) Výsledky potvrdili negativní prognostický dopad CTC+ AR-V7+ ve skupině s terapií ABI/ ENZA (zkrácení PFS u CTC AR-V7+). Poprvé byla zdokumentována taky skupina CTC-pacientů (53 a 26,2 %) podstupujících léčbu u mCRCP.…”
Section: Typ Testu Prounclassified
See 1 more Smart Citation
“…In patients not willing to be treated with chemotherapy or not eligible for chemotherapy because of the respective toxicity profile, AA or enzalutamide is often used as the second-line therapy of choice. However, the second-line treatment success of AA or enzalutamide is often limited and short-lived because of cross resistance caused by, for example, alternative splicing of the androgen receptor (3,4). Novel targeted therapies with favorable toxicity profiles are therefore needed to broaden the therapeutic armamentarium.…”
mentioning
confidence: 99%